2017
DOI: 10.1016/j.psychres.2017.05.018
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of depressive symptoms on the relationship between bullying victimization and non-suicidal self-injury among adolescents: Findings from community and inpatient mental health settings in Ontario, Canada

Abstract: Although bullying victimization has been linked to a number of behavioral and emotional problems among adolescents, few studies have investigate the mechanism through which bullying victimization affect non-suicidal self-injury. The objectives of this study were to examine the effect of bullying victimization on non-suicidal self-injury and the mediating effect of depressive symptoms on the relationship between bullying victimization and non-suicidal self-injury among adolescents. Data for this study came from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
34
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 103 publications
9
34
0
6
Order By: Relevance
“…Several studies have confirmed that, as expected, victims of bullying show higher levels of depression than nonbullied adolescents [9,10,11,12], this being one of the most widely studied consequences of bullying victimization in previous research [9,10,11]. Further, it has been demonstrated that bullying victimization is followed by depression, reaching clinical levels in some cases [9].…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…Several studies have confirmed that, as expected, victims of bullying show higher levels of depression than nonbullied adolescents [9,10,11,12], this being one of the most widely studied consequences of bullying victimization in previous research [9,10,11]. Further, it has been demonstrated that bullying victimization is followed by depression, reaching clinical levels in some cases [9].…”
Section: Introductionsupporting
confidence: 55%
“…Further, it has been demonstrated that bullying victimization is followed by depression, reaching clinical levels in some cases [9]. This issue is especially worrisome considering that depression has shown to be a significant mediator in the association between bullying victimization and nonsuicidal self-injury [11] and a moderator of suicide risk [12]. In fact, bullying victims are at a higher risk of self-harm, suicidal ideation, suicidal planning, and suicide attempts than nonbullied adolescents [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two quality of care issues of considerable interest are use of physical restraints (211)(212)(213)(214)(215)(216)(217)(218) and potentially inappropriate use of antipsychotics (211)(212)(213)(214)(219)(220)(221)(222)(223)(224)(225). The Canadian Institute for Health Information (CIHI) now reports interRAI's risk adjusted quality indicators for restraint and antipsychotic use in nursing homes in seven provinces/territories.…”
Section: Home Care and Nursing Homesmentioning
confidence: 99%
“…Additional items related to control interventions (e.g., restraint use), discharge planning and resources available upon discharge were included within the inpatient assessment. InterRAI instruments have been utilized for a wide variety of children and youth with different presenting concerns [45][46][47][48][49][50][51][52], including youth in conflict with the law [53]. For the purposes of this study, only information that was common across all instruments were utilized.…”
Section: Assessment Instrumentsmentioning
confidence: 99%